Medical Informatics Education Needs Information System Practicums in Health Care Settings - Haux, R.; Ammenwerth, E.; Häber, A.; Hübner-Bloder, G.; Knaup-Gregori, P.; Lechleitner, G.; Leiner, F.; Weber, R.; Winter, A.; Wolff, A. C. (Methods of Information in Medicine, 2006)
Objectives: To report about the themes and about experiences with practicums in the management of information systems in health care settings (health information management) for medical informatics students.Methods: We first summarize the topics of the health information management practicums/projects that the authors organized between 1990 and 2003 for the medical informatics programs at Heidelberg/ Heilbronn, Germany, UMIT, Austria, as well as for the informatics program at the University of Leipzig, Germany. Experiences and lessons learned, obtained from the faculty that organized the practicums in the past 14 years, are reported.Results: Thirty (of 32) health information management practicums focused on the analysis of health information systems. These took place inside university medical centers. Although the practicums were time-intensive and required intensively tutoring students with regard to health information management and project management, feedback from the students and graduates was mainly positive.Discussion: It is clearly recommended that students specializing in medical informatics need to be confronted with real-world problems of health information systems during their studies.
Keywords: Medical informatics; health informatics; hospital information systems; health information systems; education